Evaluation of phase change materials for personal cooling applications - Teunissen, L.; Janssen, E.; Schootstra, J.; Plaude, L.; Jansen, K. (Clothing and Textiles Research Journal, 2023)
Eleven phase change materials (PCMs) for cooling humans in heat-stressed conditions were evaluated for their cooling characteristics. Effects of packaging material and segmentation were also investigated. Sample packs with a different type PCM (water- and oil-based PCMs, cooling gels, inorganic salts) or different packaging (aluminum, TPU, TPU + neoprene) were investigated on a hotplate. Cooling capacity, duration, and power were determined. Secondly, a PCM pack with hexagon compartments was compared to an unsegmented version with similar content. Cooling power decreased whereas cooling duration increased with increasing melting temperature. The water-based PCMs showed a >2x higher cooling power than other PCMs, but were relatively short-lived. The flexible gels and salts did not demonstrate a phase change plateau in cooling power, compromising their cooling potential. Using a TPU or aluminum packaging was indifferent. Adding neoprene considerably extended cooling duration, while decreasing power. Segmentation has practical benefits, but substantially lowered contact area and therefore cooling power.